Molecular rareza: reading science in literature with Rosa Chacel's Memorias de Leticia Valle. (3rd April 2021) - Rankin, Tess C.
ABSTRACT: This article has two aims: to argue for use of the Spanish term rareza as a critical concept, and to explore the relation between popular scientific discourse and gendered ways of being and feeling in the world. The first aim is premised on curiosity about where new critical and theoretical lenses might emerge from in Spanish cultural studies. In turning to the concept of rareza, I build on the figure of the chica rara, a term originally coined by Carmen Martín Gaite in the 1980s to refer to girls who did not fit the gender expectations of the early Franco dictatorship: I posit that this Spanish cultural term could be developed to think about the strangeness of gender outside of its original context. Here, I read Rosa Chacel's 1945 novel, Memorias de Leticia Valle, specifically analyzing the construction of its young protagonist's gendered strangeness. To do so, I turn to scientific discourse popularized in the early decades of the twentieth century in Spain – when the novel is set and when Chacel, born in 1898, was formed intellectually – to understand what it might mean to think about the gender of young women as materially, relationally, affectively and perceptually strange. My consideration of the molecular chica rara as one whose experience of gender can be understood as shaped by scientific ideas is one way to rethink rareza beyond the term's original context and to consider its relevance alongside today's theorization of queerness.